2012
DOI: 10.1104/pp.112.207720
|View full text |Cite
|
Sign up to set email alerts
|

RhNAC2 and RhEXPA4 Are Involved in the Regulation of Dehydration Tolerance during the Expansion of Rose Petals

Abstract: Dehydration inhibits petal expansion resulting in abnormal flower opening and results in quality loss during the marketing of cut flowers. We constructed a suppression subtractive hybridization library from rose (Rosa hybrida) flowers containing 3,513 unique expressed sequence tags and analyzed their expression profiles during cycles of dehydration. We found that 54 genes were up-regulated by the first dehydration, restored or even down-regulated by rehydration, and once again up-regulated by the second dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 114 publications
1
118
0
Order By: Relevance
“…There is increasing evidence demonstrating that expansins are involved in the responsive mechanisms of plant species to water stress (Dai et al, 2012;Zhao et al, 2012;Barcia et al, 2014). Recently, Zhou et al (2015) have suggested that water stress inhibits leaf growth; however, changes in expansin activity and cell wall susceptibility to expansin during times of water deficit could increase the growth rate after rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence demonstrating that expansins are involved in the responsive mechanisms of plant species to water stress (Dai et al, 2012;Zhao et al, 2012;Barcia et al, 2014). Recently, Zhou et al (2015) have suggested that water stress inhibits leaf growth; however, changes in expansin activity and cell wall susceptibility to expansin during times of water deficit could increase the growth rate after rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…The EMSA was performed as described previously (Dai et al, 2012). Expression of the GST-RhHB6 fusion protein was induced in 100-mL cultures of transformed E. coli BL21 cells (see above) by addition of isopropylthio-b-galactoside to a final concentration of 0.2 mM, before the cultures were incubated at 20°C for 6 h. The recombinant proteins were extracted from the cells and purified using glutathione Sepharose 4B beads according to the manufacturer's instructions (GE Healthcare).…”
Section: Purification Of Gst-rhhb6 Recombinant Protein and Emsamentioning
confidence: 99%
“…Silencing of RhPR10.1 and RhHB6 in petal discs and plantlets by VIGS was conducted as described previously Dai et al, 2012;Tian et al, 2014), but with some modifications. The pTRV1, pTRV2, pTRV-RhPR10.1, and pTRV-RhHB6 vectors were transformed into Agrobacterium tumefaciens strain GV3101.…”
Section: Vigsmentioning
confidence: 99%
“…Similarly, genes encoding multiple NAC TFs such as NAC062, NAC052, NAC2, and NAC1 were upregulated in the super ovary (Fig. 9C), including the homolog of RhNAC2 (Csa3G852460) that regulates cell expansion through binding to the promoter of RhEXPA4 in rose petals and Arabidopsis (Dai et al, 2012). These data suggested that the enlarged petal size in the super ovary may be caused by increased cell proliferation and cell expansion mediating by TCP and NAC TFs.…”
Section: Transcriptomic Differentiation Of the Normal And Super Ovarimentioning
confidence: 69%
“…Cell wall extensibility is believed to be a limiting factor for petal expansion (Yamada et al, 2009b). The expressions of genes related to cell wall function such as those that encode xyloglucan endotransglucosylase/hydrolase and expansins are positively correlated with the petal growth during flower opening (Harada et al, 2011;Dai et al, 2012;Shinozaki et al, 2014). Hormones, including ethylene, gibberellins, and auxin, regulate petal growth and flower opening.…”
mentioning
confidence: 99%